A mixed methods study protocol for CONFIVAC, an intervention to enhance paediatric nurses' and paediatricians' skills to promote vaccination and vaccine confidence - Elisabet Henderson; Sara Valmayor; Victoria Porthé; Alba Asensio; Xavier Bruna; Usue Elizondo-Alzola; Anna Ramirez-Morros; Gemma Ricós; Josep Vidal-Alaball; M. Isabel Pasarín; Cristina Rius; Elena Roel; et al. (Vaccine: X)
Background: Vaccine hesitancy (VH), defined as the delay in acceptance or refusal of vaccination despite its availability, is a global health threat. Paediatric healthcare workers (PHCWs) are key in promoting vaccination but often feel unprepared to manage VH effectively. We developed CONFIVAC, an intervention designed to strengthen the knowledge, self-efficacy, and skills of PHCWs in improving childhood vaccination, addressing VH, and fostering a culture of immunization within primary care. This study protocol outlines the design, contents, planned implementation, and mixed-methods effectiveness evaluation of CONFIVAC. Methods: We will conduct a two-arm parallel cluster randomised controlled trial including PHCWs from 74 paediatric primary healthcare teams from Catalonia, Spain. Paediatric teams will be randomly assigned to the intervention or control arm (standard care). PHCWs in the intervention arm will participate in the training program CONFIVAC, which includes 10 h of online learning and 2 h of in-person training featuring role-playing exercises. Grounded in health behaviour theories, the curriculum includes evidence-based strategies to improve vaccination uptake. It addresses key topics such as vaccine knowledge, communication strategies, and organizational tools to promote vaccination. Process evaluation will assess overall satisfaction, likelihood of recommending CONFIVAC, and applicability. Main effectiveness outcomes will include vaccine-promoting behaviours (presumptive communication, anticipation of upcoming vaccines, and explicitly recommending vaccination in VH cases) and self-perception of having sufficient training to handle VH. We will perform adjusted ordinal regression models using an intention-to-treat approach. Quantitative results will be triangulated with qualitative insights from focus groups of PHCWs in the intervention arm employing a phenomenological approach. Discussion: CONFIVAC is expected to provide PHCWs with evidence-based knowledge, communication techniques, and organizational skills to address VH and promote vaccination. By enhancing their skills and confidence, we aim to improve vaccination uptake and streamline vaccine-related tasks in primary care settings.Trial registration: ClinicalTrials ID: NCT06489236